Combined LM and SEM studies of Cretaceous (apt-albian) spores and pollen from central Mongolia - Odgerel, Nyamsambuu; Ichinnorov, Niiden; Hofmann, Christa (Geological Issues, 2023)
The coal-bearing strata from Mongolia (Tevshiingovi Formation) of Albian to middle Aptian age contain next to dominating spores of Bryophytes and ferns, Pinaceae, Cupressaceae and Ginkgoaceae pollen only few taxa that can be affiliated with angiosperms and angiosperm-like pollen. The coal-bearing strata of the Khovil-Tugrug coal mine is located in central Mongolia southeast of Ulaanbaatar in the Choir-Nyalga basin (Figure.1) and its stratigraphic range is confined by the presence of various spores Pilosisporites notensis, Osmundacidites wellmanii, Aequitriradites spinulosus, Taurocusporites reduncus, Todisporites minor, Densoisporites sp, Cicatricosisporites australiensis, Cicatricosisporites dorogensis, Cyathidites australis, Leptolepidites verrucatus, Lycopodiumsporites sp., Lycopodiumsporites marginatus and pollen as a Podocarpites multisimus, Podocarpidites décorus, Piceapollenites sp., Pinuspollenites oralicus, Pinuspollenites sp., Alisporites sp., Cycadopites sp., Ginkgocycadophytes sp., Araucariacites australis, Araucariacites sp., Inaperturapollenites sp., Taxodiaceaepollenites sp., Classopollis classoides and angiosperm Clavatipollenites, Retimonocolpites, Liliacidites-like, Platanus-like (Bratseva, G.M. Novodvorskaya, I.M.1975; Masamichi Takahashi., 1997; Punt, W., Hoen, P.P., Blackmore,S.,Nilsson, S.& Le Thomas,A. 2007; Hesse.M, Halbritter.H, Zetter, R, 2009) (Fig. 1-7).